Community empowerment in building technical planning as an effort to improve the quality of village infrastructure - Fajar Susilowati; Arrizka Yanuar Adipradana; Evi Puspitasari (Community Empowerment, 2023)
Provision of village funds requires preparation starting from proper planning, monitoring and evaluation to improve the welfare and economic level of the community. Dusun Karaharjan Rt 02 Rw 03 Gunungpring Village, Magelang, Central Java, is one of the areas that received village funds. Nevertheless, some of the funds are still underutilized. Therefore, in order for these village funds to be managed independently and effectively, the community is taught various skills such as reading and understanding working drawings, breaking down the scope of work, calculating the volume of work, analyzing unit prices, and making a comprehensive budget plan for construction work. The method used in this activity is a holistic implementation approach. Through this activity, an increase in knowledge and skills regarding technical building planning is obtained so that it is expected to improve the quality of village infrastructure.